Optimized Concentration of Redox Mediator and Surface Protection of Li Metal for Maintenance of High Energy Efficiency in Li-O-2 Batteries - Kwak, Won-Jin; Park, Seong-Jin; Jung, Hun-Gi; Sun, Yang-Kook (WILEY-V C H VERLAG GMBH, 2018)
Recently, various approaches for adding redox mediators to electrolytes and introducing protective layers onto Li metal have been suggested to overcome the low energy efficiency and poor cycle life of Li-O-2 batteries. However, the catalytic effect of the redox mediator for oxygen evolution gradually deteriorates during repeated cycling owing to its decomposition at the surfaces of both the oxygen electrode (cathode) and the Li metal electrode (anode). Here, optimized Li-O-2 batteries are designed with a continuously effective redox mediator and a stable protective layer for the Li metal electrode by optimizing the LiBr concentration and introducing a graphene-polydopamine composite layer, respectively. These synergistic modifications lead to a reduction of the charge potential to below 3.4 V and significantly improve the stability and cycle life of Li-O-2 batteries. Consequently, a high energy efficiency of above 80% is maintained over 150 cycles. Herein, it is confirmed that the relationships between all the battery materials should be understood in order to improve the performance of Li-O-2 batteries.
Keywords: LITHIUM-OXYGEN BATTERIES; SOLID-STATE; CYCLING STABILITY; PERFORMANCE; ELECTROLYTE; LAYER; ANODE; CATHODE; GRAPHENE; POLYMER